Authenticity and Interpretation for the Personal Appropriation of Heritage in Museums - Benente, Michela; Minucciani, Valeria (Protection of Cultural Heritage, 2022)
This chapter discusses theoretical approaches to accessibility, and transitions to the broader topic of inclusion, speciﬁcally referring to museums. The contribution stresses knowledge about audiences, which is necessary to foster inclusivity and overcome “dedicated” mediation tools and activities, aiming at (re)conquering disaffected and unused publics. It also identiﬁes certain misunderstandings, e.g. regarding “cultural accessibility” and “persons with difﬁculties.” This chapter underlines the following constraints and opportunities in access to culture: authenticity and interpretation; interpretation as a hermeneutic circle involving different conﬁgurations of the sender-receiver-context triad; importance of the spatial context of communication as the ﬁrst element in interpretation or mediation; accessibility to cultural contents (importance of the physical, social and economic context; the role of cognitive processes; the importance of the individuals cultural background; emotional involvement; and ﬁnally, references to recent neurophysiological research conducted by the authors. In this contribution, authors argue cultural accessibility to be a self-appropriation process, both intellectual and emotional: predominantly individual but closely interconnected with relational processes. Cultural appropriation intended in this way has nothing to do with political and social claims but should rather constitute the ultimate goal of heritage communication. Finally, the chapter highlights possible perspectives that require dedicated professional paths, updated composition of staff (the ﬁgure of architects-museographers as a permanent presence, since communication cannot be separated from the space in which it takes place); and new good practices.